Reproductive Fiqh: The Phenomenon of Egg Freezing Among Muslim Societies - Iffatin Nur; Umi Nurul Laelatul’zah; Siti Marpuah (KARSA Journal of Social and Islamic Culture, 2022)
This study was intended as a response to the egg freezing phenomenon, a growing issue among contemporary society, through the formulation of fiqh of reproduction. As seen in the culture of contemporary society, technological advancement affecting the culture of people is an inevitability. Along with the advancement of technology in today's contemporary era, the phenomenon of egg freezing and its impacts cannot be ignored. As in the study of Islamic law (fiqh), every action is always considered to have an impact caused by the act, both positive and negative. This study used a literature review with data on the phenomenon of egg freezing as a new reproductive phenomenon in contemporary society. The data then became the basis for interpreting the concept of the principle of maqashid sharia in the study of ushul fiqh as the basis for the formulation of fiqh of reproduction. The findings in this study show that egg freezing according to the study of fiqh of reproduction may be performed with the right reasoning of benefit for women.